Experimental Study on the Oil Recovery Performance of CO2 Huff-and-Puff Process in Fractured Tight Oil Reservoirs. (3rd March 2022) - Qian, Kun; Huang, Yu; He, Yanfeng; Dou, Xiangji; Wu, Xiaojun
Abstract : In order to investigate energy supply capacity and oil production contribution of near-fracture and fracture-free zone in fractured tight oil reservoirs, a series of CO2 huff-and-puff tests were designed and carried out in different experimental conditions. A fracture-matrix long-core system was established to simulate the near-fracture zone and matrix zone of tight oil reservoirs. The NMR technique was utilized to identify the microscopic remaining oil of certain core samples. The effects of fracture length, soaking time, depressurization method, and asphaltene precipitation on the oil recovery performance of CO2 huff-and-puff process were evaluated, respectively. The results indicated that the dissolution and diffusion range of the injected CO2 can be apparently increased from both macro and micro aspects through increasing the length or density of the fractures and extending the soaking time; and, during puff period, the slow depressurization method has better recovery effect on near-fracture zone, while the step depressurization method has better recovery effect on distal fracture-free matrix. After CO2 huff-and-puff process, the oil recovery of the medium pores near fracture could be close to oil recovery of the large pores, which is higher than 60%. But, in the distal matrix, the oil recovery of the medium pores was only a little higher than depletion development. The remaining oil of medium pores in distal fracture-free matrix still has great potential to be developed after CO2 huff-and-puff process.